Strand 2: Towards a Multi-Agent Framework to Assist Networked. Learning - Stamatis, D.; Kefalas, P.; Kargidis, T. (Proceedings of the International Conference on Networked Learning, 1998)
Through the continuously evolving information technologies, Networked Learning (NL) has set the scene cowards an effective and low cost Open and Distance Learning (ODL) scheme. It is argued that Artificial Intelligence (AI) provides a technology which is already available and also has the potential to support NL both at the organisational and educational level. This paper proposes a framework based on multiple AI agents which can be used to automatically or semi-automatically assist various stages of NL. This assistance is indented for both learners and course providers who need to carry out specific casks before, during and after the delivery of a course. The architecture of such a multiagent system is presented and the processes which are automatically supported are briefly discussed.